The Effect Of Company Financial Performance On Stock Prices With Dividend Payout Ratio As Intervening Variables In Food And Beverage Sector Companies - Jakataofik, Iik; S. Paranita, Ekayana; Ispriyahadi, Heri (International Journal of Science, Technology & Management, 2023)
The food and beverage industry (Food & Beverages Sector) is part of a rapidly growing manufacturing company in Indonesia. If measured by the number of companies listed on the Indonesia Stock Exchange from time to time, it is increasing. Food and beverage companies were chosen because they play an important role in meeting consumer needs, especially during the COVID-19 pandemic. Food and beverage companies are still alive compared to other sectors. This study aims to determine the effect of the company's financial performance on stock prices with the dividend payout ratio as an intervening variable in the food and beverage sector companies. Dethe science used is researchcausal associative (Causal Relationship) andcomparative. The type of data used in this survey is secondary data, with a sample of 14 2015-2021 annual reports of food and beverage companies listed on the IDX.This research uses SPSS and SmartPLS 3 software methods.Hasil from the study shows that solvency and activity have a significant effect on dividend payout ratioi and stock prices, while profitability and liquidity have no significant effect on dividend payout ratios and stock prices. Dividend payout ratio has an effect on stock pricesin food and beverage sector companies on the IDX. Bmeans Dividend payout ratio has an effect on stock prices. Financial performance, which consists of solvency and activity, has an indirect effect on stock prices mediated by the dividend payout ratio, while profitability and liquidity have no indirect effect on stock prices mediated by the dividend payout ratio. There is no significant difference between the average stock pricesfood and beverage companies before and during the covid-19 pandemic in Indonesia.